The incidence and influencing factors of recent suicide attempts in major depressive disorder patients comorbid with moderate-to-severe anxiety: a large-scale cross-sectional study - Lina Ren; Yeqing Dong; Xiaojing Zhou; Chuhao Zhang; Jiajia Gao; Lulu Li; Xiao Zhang; Min Zeng; Guoshuai Luo; Xiangyang Zhang (BMC Psychiatry)
Abstract Background Major depressive disorder (MDD) is a recurrent and persistent mental illness. However, there is a lack of research that distinguishes the severity of comorbid anxiety disorders in MDD, and insufficient evidence exists regarding the prevalence of MDD patients with comorbid moderate-to-severe anxiety in the Chinese population. Methods The study included 1718 MDD patients (894 with moderate-to-severe anxiety symptoms and 824 without moderate-to-severe anxiety symptoms). Clinical symptoms and development were assessed using the Hamilton Depression Rating Scale-17 (HAMD-17), Hamilton Anxiety Rating Scale-14 (HAMA-14), Positive and Negative Syndrome Scale (PANSS), and Clinical Global Impression (CGI). The blood pressure and thyroid hormone levels were measured. Results We found that the incidence of MDD patients with moderate-to-severe anxiety symptoms was 52.04%. The prevalence of recent suicide attempts in MDD comorbid moderate-to-severe anxiety patients was 31.8%, which was 4.24 times higher than that in patients without moderate-to-severe anxiety. Additionally, suicide attempters had elevated levels of thyroid stimulating hormone (TSH), anti-thyroglobulin (TgAb), thyroid peroxidases antibody (TPOAb), systolic blood pressure (SBP), and diastolic blood pressure (DBP) compared to non-suicide attempters. We further identified CGI score, TSH, TPOAb, and DBP as influential factors for recent suicide attempts in MDD individuals who had moderate-to-severe anxiety symptoms. These indexes could distinguish between suicide attempts and non-suicide attempts in MDD patients with moderate-to-severe anxiety symptoms. Conclusions Our findings mainly indicated a high prevalence of recent suicide attempts in MDD patients with moderate-to-severe anxiety. Several clinical correlates, thyroid hormones, and blood pressure might contribute to recent suicide attempts in MDD patients with moderate-to-severe anxiety symptoms.